Hybrid Hydrothermal Carbonization and Ultrasound Technology on Oil Palm Biomass for Hydrochar Production. Issue 1 (23rd December 2022) - Madusari, Sylvia; Jamari, Saidatul Shima; Nordin, Noor Ida Amalina Ahamad; Bindar, Yazid; Prakoso, Tirto; Restiawaty, Elvi; Steven, Soen
Abstract: The hybrid hydrothermal carbonization and ultrasound technology (HHTC‐Us) efficiently utilizes the function of both ultrasounds‐assisted and hydrothermal carbonization for hydrochar production. The HHTC‐Us of oil palm residues plays an essential role in hydrochar production. Hydrochar is a carbon‐rich material potentially produced from oil palm biomass, which has gained great interest due to its unique properties. Four main topics were highlighted: the production of crude palm oil and impacted biomass residue generation, properties and potential values of oil palm biomass conversion as hydrochar, hybrid hydrothermal carbonization reaction routes, and processing parameters that affect the HHTC‐Us technology. The review elucidates the promising production process or modification of hydrochar from oil palm biomass residues through hybrid technology. The technology potentially enhanced sustainability, creating challenges and new opportunities. Abstract : The hybrid hydrothermal carbonization and ultrasound method is described as a future green technology for producing high quantities of fabricated hydrochar. Detailed insight into the process parameters for a complex recalcitrant structure of oil palm biomass, which is abundant in plantation and a challenge in the conversion technology to obtain eco‐friendly carbonaceous materials, is provided.